Patent absurdity. - Frank, S.J.
A growing chorus of critics in the popular press has chastised software developers, Web-application designers, and gene-patenting biotechnologists, among others, for securing patent rights that-it is said-subvert the system. The patent office has been cracking down. The most notable reforms affecting bad patents are statutory changes.
Keywords: Web-application designers; Bad patents; Gene-patenting biotechnologists; Patent absurdity; Patent rights; Software developers; Statutory changes